Peripheral non-viral MIDGE vector-driven delivery of β-endorphin in inflammatory pain - Busch Melanie; Labuz Dominika; Brack Alexander; Rittner Heike L; Mousa Shaaban A; Sitte Nicolle; Binder Waltraud; Schroff Matthias; Oswald Detlef; Machelska Halina; Wittig Burghardt; Schäfer Michael; et al. (SAGE Publishing, 2009)
Abstract Background Leukocytes infiltrating inflamed tissue produce and release opioid peptides such as β-endorphin, which activate opioid receptors on peripheral terminals of sensory nerves resulting in analgesia. Gene therapy is an attractive strategy to enhance continuous production of endogenous opioids. However, classical viral and plasmid vectors for gene delivery are hampered by immunogenicity, recombination, oncogene activation, anti-bacterial antibody production or changes in physiological gene expression. Non-viral, non-plasmid minimalistic, immunologically defined gene expression (MIDGE) vectors may overcome these problems as they carry only elements needed for gene transfer. Here, we investigated the effects of a nuclear localization sequence (NLS)-coupled MIDGE encoding the β-endorphin precursor proopiomelanocortin (POMC) on complete Freund's adjuvant-induced inflammatory pain in rats. Results POMC-MIDGE-NLS injected into inflamed paws appeared to be taken up by leukocytes resulting in higher concentrations of β-endorphin in these cells. POMC-MIDGE-NLS treatment reversed enhanced mechanical sensitivity compared with control MIDGE-NLS. However, both effects were moderate, not always statistically significant or directly correlated with each other. Also, the anti-hyperalgesic actions could not be increased by enhancing β-endorphin secretion or by modifying POMC-MIDGE-NLS to code for multiple copies of β-endorphin. Conclusion Although MIDGE vectors circumvent side-effects associated with classical viral and plasmid vectors, the current POMC-MIDGE-NLS did not result in reliable analgesic effectiveness in our pain model. This was possibly associated with insufficient and variable efficacy in transfection and/or β-endorphin production. Our data point at the importance of the reproducibility of gene therapy strategies for the control of chronic pain.